2018
DOI: 10.1055/s-0037-1621714
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Tips for the Management of the Wide Nasal Base

Abstract: Alar base reduction (ABR) was first described by Weir in 1892, but continues to be a controversial topic in rhinoplasty in terms of optimal techniques. The authors describe the techniques for ABR including internal, external and combined ABR, flare excisions, and alar hooding reductions. The techniques described have resulted in consistent outcomes with acceptable scarring and high patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Alar base surgery should be approached conservatively, because once it is performed, it cannot be easily reversed. If the amount of reduction is insufficient, an additional excision should be performed in future [8].…”
Section: Discussionmentioning
confidence: 99%
“…Alar base surgery should be approached conservatively, because once it is performed, it cannot be easily reversed. If the amount of reduction is insufficient, an additional excision should be performed in future [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, residual columellar incision scars or possible deformities due to scar formation are the main disadvantages of this technique. Scar formation is influenced by factors such as incision and closure method, as well as postoperative care (1)(2)(3)(4). Previous studies have shown that absorbable sutures can be used safely in the columella without any long-term cosmetic concerns or an increased infection risk (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…We have a few evaluation tools that numerically and objectively measure the changes we make in patients. 3 4 5 6 7 8 9 Human beings make a self-image based on imagination. For this reason, it is logical to think that all the elements: photographs and 3D images will improve patient–doctor communication, potentially simplifying the expectations of the patient and those of the surgeon.…”
Section: Introductionmentioning
confidence: 99%